Faktor yang Memengaruhi Financial Distress - Laudiantika, Resti; Mahroji, Mahroji (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
Financial distress represents a critical condition that threatens a company’s sustainability due to difficulties in fulfilling its financial obligations. In Indonesia, the property sector has been particularly vulnerable, especially in the post-COVID-19 period marked by declining markets and reduced consumer purchasing power. This study aims to provide empirical evidence on the effects of liquidity (CR), debt policy (DER), and leverage ratio (ICR) on financial distress, measured by the Altman Z-Score. Using a quantitative approach, multiple linear regression analysis was conducted on secondary data obtained from the annual financial statements of property companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The sampling method applied was purposive sampling. The results reveal that liquidity (CR) has a significant positive effect on financial distress, while debt policy (DER) and leverage ratio (ICR) show significant negative effects. These findings are in line with Signaling Theory, which suggests that financial information serves as an important signal for external stakeholders in assessing corporate conditions and prospects. The study’s limitations include the restricted sample size and short observation period. Therefore, further research is recommended to expand the sectoral coverage, extend the observation period, and include additional variables such as profitability and sales growth. These variables are expected to strengthen the financial distress prediction model by representing a company’s ability to generate profits and sustain revenue growth.